The Study Of “Do” Auxiliary Produced by Indonesian Students Non-English Department - Soflies Marry Bingku (AIBPM Publisher, 2020)
“Do” is one of the very important elements in English sentence. The Students learning English often make mistakes regarding the usage of this element, although English has been learnt for more than 6 years. This research intends to study about the inter language variations produced by English learners, who are learning English as one of the required subjects. Besides the researcher has tried to describe about factors, which give both negative and positive contributions to the participants in acquiring “do” auxiliary. After analyzing and discussing all of the collected data, the conclusions are written as follows: First, the inter language variations are Missing “do” auxiliary, which is appeared only in spontaneous data and missing “did” found in Recognition test. There are problems with subject-verb-agreement, “do” is replaced by “does” or vice versa. Another tendency is also the interchangeably use between “do” and “be”, and “do” and “did”. Second, it appears that L1 and L2 gives negative influences to the participants in their progress acquiring English. The complexity of English rules makes them unable to apply the correct rules for example by applying a trend to over-generalize the English rule. Third, the input from their informal environment including social media, movies, E-book, online games and English songs gives positive contribution to the participants in acquiring “do” auxiliary. Besides memorization and imitation play good role for this case.